Factors From Middle Childhood That Predict Academic Attainment at 15–17 Years in the UK: A Systematic Review - Williams, Margiad E.; Clarkson, Susan; Hastings, Richard P.; Watkins, Richard C.; McTague, Phil; Hughes, J. Carl (Frontiers in Education, 2022)
Success in adult life is associated with end of school academic attainment, but educational inequality is a major issue in the UK. Contextual background factors and personal attributes associated with student academic attainment have been identified in cross-sectional research. However, there has not been a systematic synthesis of these factors from longitudinal studies particularly with a focus on factors from middle childhood. The aim of this systematic review was to identify factors from middle childhood (6-12 years) that are associated with academic attainment at 15-17 years. Ninety UK studies met the inclusion criteria. Factors identified related to the student, socioeconomic, academic attainment, and the school. The quality of studies was generally rated as poor, and evidence for most factors was sparse, suggesting caution in interpretation. The middle childhood factors with the strongest evidence of association with later attainment were: prior attainment at the student level, student mental health, and gender. Generally, the results supported UK Government guidance on narrowing the education inequality gap although there was a lack of high-quality studies. The findings could be potentially useful for policymakers and schools in making decisions on effective interventions, policy choices, and funding allocations, particularly in the context of a socioecological framework. However, further research is needed in this area.